Response of four oil palm varieties to low frond desiccation in the main nursery with water stress conditions on peat. Issue 1 (1st May 2022) - Muhayat,; Rauf, A; Mukhlis,; Winarna,
Abstract: Oil palm is an important commodities for plantation sub-sector in Indonesia. The limitation of mineral soils for agriculture directs utilization of peatland for oil palm plantation. The major problem of peatland plantations is Low Frond Desiccation (LFD) due to fluctuation of groundwater. This study observed the responses of oil palm in the main nursery to water stress as well as the changes in physical and physiological properties of plants. This research using factorial randomized block design, replicated three times with two factors (four oil palm varieties and five watering stoppage) to determine plant responses to watering stoppage. The results showed that watering stoppage can increase the LFD incidence, decrease leaf chlorophyll, water content and plant height. The highest incidence and LFD intensity was at 5 weeks watering stoppage with the highest LFD intensity value of 45.67%. LFD started at 2 weeks watering stoppage with LFD intensity ranging from Dumpy variety 17.69%, DxP 540 variety 28.58%, Langkat variety 29, 46%, Yangambi variety 38.89%. The oil palm varieties having the highest LFD intensity at 5 weeks watering stoppage were found in the Yangambi variety and the lowest was in the Dumpy variety.